2015 ASEE Annual Conference and Exposition Proceedings
DOI: 10.18260/p.23707
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Ph.D. Programs in Engineering Education

Abstract: is an Associate Professor of Engineering Education at Virginia Tech, where she also serves as co-Director of the VT Engineering Communication Center (VTECC). Her research interests include interdisciplinary collaboration, design education, communication studies, identity theory and reflective practice. Projects supported by the National Science Foundation include exploring disciplines as cultures, interdisciplinary pedagogy for pervasive computing design; writing across the curriculum in Statics courses; as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 1 publication
0
18
0
Order By: Relevance
“…The information given here is based on the papers by Benson et al [7] and Murzi, Shekhar and McNair [12]; on the information collected during our visit to Virginia Tech and Purdue; and on the websites of the five programmes. This study has the limitation that no confirmation is available about the validity of some information (especially from those European Universities where information exists in English, but some information is available only in their own languages, about which the authors cannot speak).…”
Section: Training Courses Of the Studied Programmesmentioning
confidence: 99%
“…The information given here is based on the papers by Benson et al [7] and Murzi, Shekhar and McNair [12]; on the information collected during our visit to Virginia Tech and Purdue; and on the websites of the five programmes. This study has the limitation that no confirmation is available about the validity of some information (especially from those European Universities where information exists in English, but some information is available only in their own languages, about which the authors cannot speak).…”
Section: Training Courses Of the Studied Programmesmentioning
confidence: 99%
“…Engineering education research is a new and growing discipline that aims to improve the retention and professional skill/competency development of engineering students worldwide. Several US universities have engineering education centers, departments, and doctoral programs to train students and support engineering faculty in their research and pedagogy (Murzi et al, 2015). This is one of the first studies to examine why engineering education researchers may experience impostor phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…The creation of the initial departments of engineering education enabled the development of individuals with expertise in engineering education research and the interest to prepare these researchers has grown. As of 2015, there were only four programs identified that had a PhD or Doctorate degree in Engineering Education based on the following departmental/program qualifications: (1) a degree offered by an engineering school or college, (2) had alumni, and (3) had been operating for at least five years [6]. Yet, over the past five years, there are many more up and coming doctoral-based programs that are currently in operation or under development [7].…”
Section: Introductionmentioning
confidence: 99%